\(\dfrac{x}{2x-6}-\dfrac{x}{2x+2}=\dfrac{2x}{\left(x+1\right)\left(x+3\right)}\)
\(\Leftrightarrow\) \(\dfrac{x}{2\left(x-3\right)}-\dfrac{x}{2\left(x+1\right)}=\dfrac{2x}{\left(x+1\right)\left(x-3\right)}\)(đk: x \(\ne\)-1; x \(\ne\)3)
\(\Leftrightarrow\)\(\dfrac{x\left(x+1\right)}{2\left(x-3\right)\left(x+1\right)}-\dfrac{x\left(x-3\right)}{2\left(x+1\right)\left(x-3\right)}=\dfrac{4x}{2\left(x+1\right)\left(x-3\right)}\)
\(\Leftrightarrow\) x(x + 1) - x(x - 3) = 4x
\(\Leftrightarrow\) x2 + x - x2 + 3x = 4x
\(\Leftrightarrow\) 3x - 4x = 0
\(\Leftrightarrow\) -x = 0
\(\Leftrightarrow\) x = 0 (tmđk)
Vậy phương trên có n0 là x = 0